Peningkatan Kemampuan Pemecahan Masalah dan Motivasi Siswa Melalui Pembelajaran Discovery Berbasis Proyek Pada Materi Sistem Reproduksi di Kelas IX SMP - Sugono Sugono (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The objectives of this study was (1) To find out the implementation of project-based discovery learning model for reproductive system material in living things in grade IX junior high school (2) Analyze whether there is an increase in students' problem-solving abilities after going through project-based discovery model learning for reproduction system material in creatures life in class IX SMP, (3) Knowing whether there is an increase in student motivation through learning a project-based discovery model for the reproductive system material in living things in class IX SMP. This research is a classroom action research. The research design used the Kemmis & Tagart stages which consist of 4 stages (1) planning, (2) implementation, (3) Observation, and (4) Reflection. The sample of this research is grade IX students of SMP Negeri 2 Kapetak Cirebon. Data collection techniques used test techniques and observation sheets. Data analysis techniques used descriptive analysis. The results of the study concluded that (1) The implementation of project-based discovery learning model for reproductive system material in KD 4.1 presents the results of information retrieval from various health-related sources and efforts to prevent disorders of the reproductive organs in class IX students at SMP Negeri 2 Kapetakang Cirebon reaching 92.5% with a very good category, (2) There is an increase in students' problem solving abilities by using a project-based discovery learning model on the basic competencies 4.1 class IX in SMP Negeri 2 Kapetak Cirebon in the academic year 2019/2020. This is evident from an increase in the average value of learning outcomes and the value of classical completeness. (3) There is an increase in student motivation in class IX SMP Negeri 2 Kapetakan Cirebon after discovery learning based on the KD 4.1 project basic competency presents the results of information retrieval from various sources related to health and efforts to prevent disorders of the reproductive organs.